Perancangan dan Pembuatan E-Commerce pada Toko M - Stephanus Tantiono; Silvia Rostianingsih; Victor Julian Lipesik (Jurnal Infra, 2017)
M Store is a company engaged in field of textile and fashion in Surabaya. Lack of promotion by Store M lead to potential of the market is less excavated. Therefore, M Store develop marketing through internet with open an online store through marketplace to reach wider markets or segments. But competition in internet is very tight and need added-value to compete. With making of e-commerce website expect to help build assets and branding of M Store.This thesis was designed with Data Flow Diagram and Entity Relationship Diagram. E-commerce system is built using PHP and MySQL database. From implementation, generating facilities such as store information, products, blogs and news, discussions, reviews, and purchase through website. M Store’s admins can develop through backsite website, so admins can process transactions and content of website with an easy interface. From the making of M Store’s e-commerce can be drawn some conclusions like, the website gets 95.2% to mainsite and 97.5% for backsite and this application have met the needs of M Store and M Store’s consumer.